Enhancing Network Security in Libya: Challenges, Current Status, and Future Directions - Abier Saleh Belashher (المجلة الأفروآسيوية للبحث العلمي, 2025)
Network security is essential for protecting sensitive information, ensuring operational continuity, and building trust in digital services. In Libya, rapid digital adoption amid political instability and limited cybersecurity infrastructure has increased vulnerability to cyber threats. Strengthening cybersecurity is crucial to safeguard sensitive data, secure critical infrastructure, foster public trust in digital services, and support Libya’s digital economy. Assessing awareness levels among individuals and organizations provides an evidence-based foundation for strategic interventions. This study aimed to evaluate the current cybersecurity landscape in Libya, identify awareness gaps among individuals and organizations, and propose practical measures to enhance national network security. A cross-sectional mixed-methods design was used. Data were collected through structured questionnaires administered to 300 participants, and 18 online semi-structured interviews with IT managers and cybersecurity policymakers. Quantitative data were analyzed using descriptive statistics, while qualitative interview data underwent thematic content analysis to identify key challenges and opportunities. Survey results indicated weak password usage (60%), low adoption of multi-factor authentication (30%), limited formal cybersecurity training (20%), and low use of advanced security tools (25%). Online interviews highlighted policy gaps (83%), insufficient trained professionals (78%), and high exposure of critical infrastructure sectors. Libya’s cybersecurity environment remains fragile, with significant gaps in user and organizational awareness, policy frameworks, and technical resilience. Comprehensive interventions, including capacity building, policy reform, ICT infrastructure investment, incident reporting systems, and international collaboration, are essential to enhance digital resilience, protect sensitive data, and support the growth of Libya’s digital economy.